Advancements and Challenges in Tongue Transplantation: A Comprehensive Review and Meta‐Analysis (A Systematic Review) - Manea, Hashim; Alhatemi, Ahmed Qasim Mohammed; Sulaiman, Fatimah Abdullah; Hashim, Ali Talib; Al‐Ghuraibawi, Mohammedbaqer Ali (Health science reports, 2025)
ABSTRACT Background and Aims Tongue transplantation is emerging as a novel reconstructive option aimed at restoring critical functions—such as articulation, swallowing, and taste—in patients with extensive tongue defects due to squamous cell carcinoma or trauma. This systematic review and meta‐analysis synthesizes current clinical outcomes, challenges, and future directions in tongue transplantation. Methods A comprehensive literature search was performed in PubMed, Google Scholar, Medline, Cochrane, Web of Science, and ScienceDirect from January 2000 to August 2020, using predefined Boolean combinations of keywords (e.g., “Tongue Transplant,” “Tongue Reconstructive Surgery”). Studies were screened and selected according to PRISMA guidelines. Six studies meeting strict inclusion criteria—providing detailed patient demographics, surgical techniques, and outcomes (totaling 51 patients)—were included. Data extraction and quality assessment were performed independently by three reviewers. Meta‐analysis was conducted using Review Manager 5.4 and Jamovi 2.4.1.0. Heterogeneity was assessed with the I² statistic; for I² values ≥ 50%, a random‐effects model was used. Statistical significance was defined as p < 0.05 (two‐sided tests), with effect sizes and 95% confidence intervals reported. Results Analysis revealed substantial heterogeneity among studies (I² = 85%, p < 0.001). Overall, tongue transplantation was associated with improved functional outcomes—such as restoration of swallowing and partial recovery of taste sensation—with variable degrees of success. Detailed comparative analysis of surgical techniques, donor selection, and immunosuppressive protocols highlights both common benefits and notable challenges, including technical complexity and risks related to immunosuppression. Conclusion Tongue transplantation shows promise in significantly improving quality of life in select patients; however, technical, immunological, and reinnervation challenges remain. Future research should focus on refining surgical protocols, exploring tissue engineering alternatives, and standardizing post‐transplant care to optimize long‐term outcomes.